Source follower-based high-speed switched capacitor amplifier for pipelined ADCs - Siek, Liter (2015)
A low-power high-speed source follower-based switched capacitor (SC) amplifier for pipelined analogue-to-digital converters (ADCs) is proposed. Using the source follower as the core of the SC amplifier, the power consumption can be significantly reduced while obtaining the same linearity and bandwidth. Meanwhile, through replicating the input signal to the drain of the input transistor, the channel-length modulation effect can be suppressed, achieving a high linearity (>60 dB). The functionality and linearity of the proposed SC amplifier are verified by simulation results.